Energy-Efficient Hydraulic System for Hexapod Robot Based on Two-Level Pressure System for Oil Supply - Junkui Dong; Bo Jin; Ziqi Liu; Lei Chen (Biomimetics)
This article proposes a two-level pressure system (TPS) inspired by mammalian energy supply mechanisms to enhance the energy efficiency of hydraulic hexapod robots (HHRs), In contrast to traditional one-level pressure systems (OPSs), the TPS contains both high-pressure and low-pressure oil supplies, which can switch the oil supply pressure according to the actuator load to reduce throttling loss and improve energy efficiency. Additionally, the TPS adopts a separate-meter-in and separate-meter-out (SMISMO) method to manage flow and pressure switching for the actuators. This article also analyzes the energy transfer process of an HHR and establishes kinematic and hydraulic system models. The energy-saving and control performance of the TPS is verified through simulations and experiments. The results show that compared to the OPS, the TPS achieves a 28.8% reduction in energy consumption while imposing higher demands on control performance.